Program Interaksi Sosial Umat Beragama Islam dan Hindu di Kawasan Pantai Loang Baloq Perwujudan Keharmonisan Dalam Keragaman: The Social Interaction Program of Muslims and Hindus in the Loang Baloq Beach Area is the Realization of Harmony in Diversity - Dewi, Ni Luh Sinar Ayu Ratna; Ni Putu Sasmika Dewi; Ni Komang Wiasti; I Wayan Wirata; Suci Raditya Yadnya; Yadnya, Made Sutha (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Loang Baloq Beach in Mataram City, West Nusa Tenggara, is one of the religious tourism destinations and also a real symbol of harmony between religious communities. This service aims to examine the forms of interfaith Islamic and Hindu social interaction that occur in the region, analyze how the impact of the release of birds, fish and hatchlings on the Loang Baloq Beach ecosystem and the supporting factors for the realization of harmony in diversity. Loang Baloq Beach according to the local Sub-district Head (Cahya Samudra) and the local Village Head (Haji Gunawan) stated that it is often also used as an alternative place to carry out the Eid Topat Ceremony or known as Eid Ketupat, which is a unique tradition of the Sasak tribe community as a form of tolerance for Muslims and Hindus. For Hindus, it is customary to carry out the melasti (purification) ceremony of melasti and the removal of ashes after burning or ngaben. As well as in the field of art in the form of kite competitions for the younger generation to show their talent through positive things in the form of kite art. The methods used in this study are a qualitative approach with participatory observation techniques of the IAHN Gde Pudja Mataram Academic Community, in-depth interviews with local regional leaders, release of hatchlings and fish on the beach with local communities, and documentation studies. The results of the study show that the practice of tolerance at Loang Baloq Beach is reflected in the implementation of mutual respect religious rituals, interfaith participation in traditional and social activities, and the existence of local wisdom values that are inherited from generation to generation. In addition, this area also functions as a mediation space between different religious communities through common cultural practices, such as pilgrimage and Maulid celebrations. This finding strengthens the position of Loang Baloq Beach as a model of social harmony based on local values and spirituality. This service is expected to contribute to strengthening religious moderation and the development of tolerance-based tourism.